2016
DOI: 10.1016/j.ydbio.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Zfrp8 forms a complex with fragile-X mental retardation protein and regulates its localization and function

Abstract: Fragile-X syndrome is the most commonly inherited cause of autism and mental disabilities. The Fmr1 (Fragile-X Mental Retardation 1) gene is essential in humans and Drosophila for the maintenance of neural stem cells, and Fmr1 loss results in neurological and reproductive developmental defects in humans and flies. FMRP (Fragile-X Mental Retardation Protein) is a nucleo-cytoplasmic shuttling protein, involved in mRNA silencing and translational repression. Both Zfrp8 and Fmr1 have essential functions in the Dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Tsr4 is evolutionarily conserved among eukaryotes (30). PDCD2/Zfrp8 in Drosophila directly interacts with Rps2, is both cytoplasmic and nuclear, and appears to serve a function in 40S production, but the significance of its interaction with Rps2 has not been extensively characterized (29,41,49). Humans have two Tsr4 homologs, PDCD2 and PDCD2L (30), and expression of human PDCD2 can fully complement the loss of Drosophila PDCD2/Zfrp8, indicating functional conservation (49).…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
See 2 more Smart Citations
“…Tsr4 is evolutionarily conserved among eukaryotes (30). PDCD2/Zfrp8 in Drosophila directly interacts with Rps2, is both cytoplasmic and nuclear, and appears to serve a function in 40S production, but the significance of its interaction with Rps2 has not been extensively characterized (29,41,49). Humans have two Tsr4 homologs, PDCD2 and PDCD2L (30), and expression of human PDCD2 can fully complement the loss of Drosophila PDCD2/Zfrp8, indicating functional conservation (49).…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
“…In a more recent study, the Bachand group showed that PRMT3 does not cotranslationally associate with Rps2 (56), but whether or not PDCD2L or PDCD2 cotranslationally associates with Rps2 was not explored. Notably, Drosophila PDCD2/Zfrp8 copurifies with translation machinery, suggesting that cotranslational capture of Rps2 may be a conserved function of Tsr4 orthologs (41). Interestingly, the human zinc finger protein ZNF277 was identified as a cotranslational interactor of Rps2; however, knockdown of ZNF277 does not impair 40S production, suggesting that the ZNF277-Rps2 complex has a role outside ribosome biogenesis (56).…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
See 1 more Smart Citation
“…The mislocalization of BicD and Orb as well as the severe abnormalities of the Zfrp8 germ line may result from abnormal localization of their mRNA and defects in spatial translation, suggesting that Zfrp8/PDCD2 may be immediately involved in mRNA transport. Our recent studies show that PDCD2/Zfrp8 interacts with a number of proteins responsible for mRNA localization and translational repression [ 14 ] such as FMRP/Fmr1 (Fragile-X Mental Retardation Protein [ 15 ], and NUFIP1/Nufip (Nuclear FMRP-interacting Protein, [ 14 , 16 ]). FMRP has been shown to associate with NUFIP and with mRNAs in the nucleus and this RNP complex is exported into the cytoplasm, where FMRP regulates mRNA translation and degradation [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…FMRP has been shown to associate with NUFIP and with mRNAs in the nucleus and this RNP complex is exported into the cytoplasm, where FMRP regulates mRNA translation and degradation [ 17 19 ]. Zfrp8 directly binds Nufip, is required for the proper localization of FMRP to cytoplasmic puncta, and likely affects the same or overlapping RNA/mRNA targets as FMRP [ 14 ]. The genetic interaction between Fmr1 and Zfrp8 shows that they have antagonistic functions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%